2007
DOI: 10.1126/science.1139952
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Mass Spectrometry Identifies Insulin Signaling Targets in C. elegans

Abstract: DAF-2, an insulin receptor-like protein, regulates metabolism, development, and aging in Caenorhabditis elegans. In a quantitative proteomic study, we identified 86 proteins that were more or less abundant in long-lived daf-2 mutant worms than in wild-type worms. Genetic studies on a subset of these proteins indicated that they act in one or more processes regulated by DAF-2, including entry into the dauer developmental stage and aging. In particular, we discovered a compensatory mechanism activated in respons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

20
313
2
6

Year Published

2008
2008
2022
2022

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 308 publications
(341 citation statements)
references
References 21 publications
20
313
2
6
Order By: Relevance
“…Proteins whose ratios differed from the normalized median by more than 2-fold and whose relative standard errors across replicates were less than 50% were considered differentially expressed (Table 2) (see ref. 21). We identified 10 differentially expressed proteins that met these criteria; other differentially expressed proteins with greater biological variability were seen also (Table S4).…”
Section: Proteomic Comparison Of Colonic Tumors and Normal Epitheliummentioning
confidence: 99%
See 1 more Smart Citation
“…Proteins whose ratios differed from the normalized median by more than 2-fold and whose relative standard errors across replicates were less than 50% were considered differentially expressed (Table 2) (see ref. 21). We identified 10 differentially expressed proteins that met these criteria; other differentially expressed proteins with greater biological variability were seen also (Table S4).…”
Section: Proteomic Comparison Of Colonic Tumors and Normal Epitheliummentioning
confidence: 99%
“…2 Each protein was quantified in multiple mouse pairs, with a mean ratio exceeding a 2-fold change and a relative standard error of less than 50% (see ref. 21). Mean microarray expression ratios also are listed for each protein.…”
Section: Proteomic Comparison Of Colonic Tumors and Normal Epitheliummentioning
confidence: 99%
“…M uch progress has been made in mass spectrometry (MS)-based quantitative proteomics in recent years, as evidenced by numerous applications, such as biomarker discovery, 1 study of chromatin assembly and disassembly, 2 identification of insulin signaling targets, 3 and protein posttranslational modification (PTM). 4 Among the most commonly used quantitative strategies are full MS scan-based quantitation methods, such as SILAC (stable isotope labeling with amino acids in cell), 5 15 N-labeling, 6 and 18 O-labeling.…”
mentioning
confidence: 99%
“…Dissection of the insulin/IGF signalling pathway has identified sod-3 as a significant target for the DAF-16/FOXO transcription factor. Inhibition of the insulin/IGF signalling pathway results in elevated expression of sod-3 and an extension in lifespan (Murphy et al, 2003;Lee et al, 2003;Dong et al, 2007). Recently, it has been suggested that these MnSODs function in the insulin/IGF signalling pathway as physiological redox modulators rather than antioxidants (Honda et al, 2008).…”
Section: Introductionmentioning
confidence: 99%